The molecular structure of the air/water interface in the presence of soluble surfactants - Nguyen, Cuong Van (Curtin University, 2015)
The molecular structure of the air/water interface in the presence of nonionic and cationic surfactants was investigated by combining theoretical models, experimental measurements and molecular dynamics simulation. The surfactants were selected based on their relevance to chemical processes. The modeling results were successfully verified by atomistic simulations. The new insights into molecular structure provide important information for the chemical design in mineral flotation, foaming and other industrial processes.